2023
DOI: 10.1073/pnas.2301394120
|View full text |Cite
|
Sign up to set email alerts
|

Phase variation as a major mechanism of adaptation in Mycobacterium tuberculosis complex

Abstract: Phase variation induced by insertions and deletions (INDELs) in genomic homopolymeric tracts (HT) can silence and regulate genes in pathogenic bacteria, but this process is not characterized in MTBC ( Mycobacterium tuberculosis complex) adaptation. We leverage 31,428 diverse clinical isolates to identify genomic regions including phase-variants under positive selection. Of 87,651 INDEL events that emerge repeatedly across the phylogeny, 12.4% are phase-variants within HTs (0.02% of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 70 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…274 of these genes could be aligned to H37Rv by miniprot and 90% of the aligned regions overlap with annotated CDS in RefSeq. We note that although overlapping genes in different open reading frames are rare in H37Rv (0.2% of coding regions), these genes may occur in other strains and may have functional implications ( Vargas et al 2023 , Snobre et al 2024 ). PPanGGOLiN’s preference to count such genes in the pangenome is not necessarily a weakness.…”
Section: Resultsmentioning
confidence: 87%
“…274 of these genes could be aligned to H37Rv by miniprot and 90% of the aligned regions overlap with annotated CDS in RefSeq. We note that although overlapping genes in different open reading frames are rare in H37Rv (0.2% of coding regions), these genes may occur in other strains and may have functional implications ( Vargas et al 2023 , Snobre et al 2024 ). PPanGGOLiN’s preference to count such genes in the pangenome is not necessarily a weakness.…”
Section: Resultsmentioning
confidence: 87%
“…Given that indel events in the homopolymeric tract is mainly caused by strand slippage of replicative DNA polymerase 21 , these results indicate a role of mycobacterial dnaQ in DNA replication. Of note, recent studies showed that the indel events occurred in homopolymeric tract may have a strong impact on Mtb ’s pathogenesis and drug tolerance 2224 .…”
Section: Resultsmentioning
confidence: 99%
“…As such, pseudogenes sometimes comprise a substantial portion of the genome of obligate symbionts that no longer require functions provided by the host [ 2 ]. Bacteria also use pseudogenization as a means of regulation, wherein a subset of the population contains a frameshift that disables a protein’s function [ 3 ]. The number of pseudogenes can vary enormously in genomes from the same species, suggesting pseudogenization is a major mode of evolution.…”
Section: Introductionmentioning
confidence: 99%